The Role of Architectural Design in Effective Delivery of Library Services - Ossai-Ugbah, Ngozi Blessing (Qualitative and Quantitative Methods in Libraries; Vol 6 No 2 (2017): June 2017 Issue, 2019)
This study investigated the role of architectural design in effective delivery of library services: a case study of university libraries in Edo State, Nigeria. The purpose of the study was to determine the extent to which architectural library designs effective library services. The study adopted a descriptive survey research design. The population of the study was made up of 80 librarians in seven university libraries in Edo State, Nigeria. Data was collected through questionnaire and analyzed with the use of percentages. Findings reveal that librarians in university libraries in Edo State, Nigeria observed that their library architecture play the role of a learning centre with 67%. The libraries also fit into new information communication technology (26%) and a place of social capital (23%). The three characteristics that best describe the library architecture are that they are accessible (16%), functional (15%) and suitable for information technology (15%). The problem librarians face with library architecture are majorly ventilation and heat (11% respectively). The types of spaces included more in the library architecture are magazines/newspapers (9%) and individual study space (8%). The study found that space library architecture support are more of research support and students learning and development (17% respectively). The most functional spaces in the library is textbook collection (18%), cataloging (16%) and magazines/newspapers (10%). The reason these spaces are most effective is because of service (47%). Furthermore, the least functional spaces are the canteen (11%) and bindery (10%). The reason for the ineffectiveness is identified as poor design (37%). The library design was identified to help the librarians more for information research (62%). However, majority are partially satisfied with the architectural design of their university libraries (41%). This study concluded that physical remodeling and systemic redesigning of the university library architectures are important to make effective delivery of library services. This study recommends the study or architecture by student librarians and the position of an architecture librarian as a way to tackle these issues.